2022
DOI: 10.3390/ma15041354
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Microplasma Coating on AZ91 Magnesium Alloy Prepared from Electrolyte with and without the Borax Addition

Abstract: Magnesium alloys, due to their unique properties, low density and high strength properties, are becoming more frequently used in industrial applications. However, a limitation of their use may be the need to ensure high abrasive wear resistance and corrosion resistance. Therefore, magnesium alloys are often protected by applying protective coatings. The paper presents the influence of the modification of the electrolyte composition, with or without the addition of borax, on the morphology (observed by SEM meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…[16] The sunburst plot (Figure 12) represents all the possible coating categories and materials explored by various researchers during the last decade. [67,88,98,100,[113][114][115][116][117][118] The metal-based coatings are popular in composite and singlematerial coatings. However, polymer-based materials are extensively explored in the case of biodegradable and self-healing coatings.…”
Section: Overall Comparative Analysismentioning
confidence: 99%
“…[45,51,90,138,139] The deposition time of 15 min, 20% duty cycle, 600 Hz frequency, 2 A working current, and 22 AE 2 °C electrolyte temperature are the important optimum parameters reported for AZ91D coating. [116,118,138] In the MAO coating of Mg-alloys, high voltage ranging from 200 to 500 V was used in various studies. [45,51,87,116,136] However, 120 and 140 V were also used in some studies for the MAO of AZ91D alloy for biomedical applications.…”
Section: Micro-arc Oxidationmentioning
confidence: 99%
See 1 more Smart Citation